The Perceptions of New Zealand Lawyers and Social Workers About Children Being Adopted by Gay Couples and Lesbian Couples - Scherman, Rhoda; Misca, Gabriela; Tan, Tony Xing (Frontiers in Psychology, 2020)
Global trends increasingly appear to be legitimising same-gender relationships, yet international research shows that despite statutory rights to marry—and by extension, adopt children—same-gender couples continue to experience difficulties when trying to adopt. Primary among these barriers are the persistent heteronormative beliefs, which strongly underpin the unfounded myths about parenting abilities of same-gender couples. Such biased beliefs are perpetuated by some adoption professionals who oppose placing children with lesbian or gay couples. In 2013, New Zealand passed the Marriage Equality Act, making it possible for same-gender couples to legally marry—and by extension, adopt. This provided an opportunity to investigate the perceptions of New Zealand professionals about children being placed with same-gender couples, in a country often perceived to be more tolerant of LGBT people. New Zealand social workers and lawyers (an under-studied group)—the professions most likely involved in adoption—were recruited via professional bodies. Because studying perceptions and beliefs on socially sensitive topics are highly susceptible to social desirability, we designed an instrument utilizing multiple methods to assess and corroborate participants’ views about placing children for adoption with couples of the same gender. Administered online and anonymously, the survey included demographic questions, evaluation of negative-meaning and positive-meaning statements, and used a scenario describing a prospective adoptive couple whose gender was ambiguous, in the context of adopting children of varying needs. Overall, the study found that while New Zealand lawyers and social workers (N=314) had generally favourable views of gay and lesbian adoption, they still reported a preference to see children adopted by heterosexual couples over same-gender couples, within which lesbian and gay couples were preferred equally. Moreover, being religious and politically conservative were characteristics associated with more negative views toward placing children with same-gender couples. We conclude that, despite winning the rights to marry (and adopt as couples), such legislative wins might be merely the first hurdle to be overcome; normalising same-gender parenting is what needs to happen next. Our study adds to the research focused on adoption professionals in various countries, with the ultimate aim to inform practices and policies supportive of families headed by same-gender couples and formed through adoption.